2002
DOI: 10.1109/tns.2002.805429
|View full text |Cite
|
Sign up to set email alerts
|

Charge collection in SOI capacitors and circuits and its effect on SEU hardness

Abstract: Focused ion microbeam and broadbeam heavy-ion experiments on capacitors and SRAMs are used to investigate increased saturation upset cross sections recently observed in some silicon-on-insulator (SOI) integrated circuits (ICs). Experiments performed on capacitors show a very strong bias and oxide thickness dependence for charge collection. In combination with three-dimensional (3-D) simulations, these data suggest that the mechanism for charge collection in capacitors is due to perturbation of the substrate el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 15 publications
(32 reference statements)
2
10
1
Order By: Relevance
“…The charge collection efficiency is 32% and 30% respectively. These values are in good agreement with the 37% efficiency obtained in [11] for a 0.176gm thick buried oxide SOI P-type substrate capacitor from the same technology and biased at VG=+20V [12] bombarded with 50 MeV Cu projectiles.…”
Section: Introductionsupporting
confidence: 86%
“…The charge collection efficiency is 32% and 30% respectively. These values are in good agreement with the 37% efficiency obtained in [11] for a 0.176gm thick buried oxide SOI P-type substrate capacitor from the same technology and biased at VG=+20V [12] bombarded with 50 MeV Cu projectiles.…”
Section: Introductionsupporting
confidence: 86%
“…IBIC measurements showed that the induced charge is significantly larger than that expected from the region above the BOX. This observation lead to a more detailed investigation of the phenomenon [103][104][105][106] and to the theory of charge induction in MOS structures based on the Gunn theorem [23].…”
Section: Seus In Silicon-on-insulator (Soi) Srammentioning
confidence: 99%
“…An amplification effect was observed for device bias of 20 V, a possible mechanism for this effect is high field avalanche multiplication at corners of the depletion region. Recent studies into charge collection in SOI structures have shown that significant charge collection can be induced by displacement currents across the oxide [15]. Simulation of the charge collection processes for these devices are planned to gain insight into the physical origins of the multiplication effect and to study the importance of induced displacement currents.…”
Section: Discussionmentioning
confidence: 99%